Economic evaluations of pharmacist‐managed services in people with diabetes mellitus: a systematic review. Issue 4 (28th October 2015) - Wang, Y.; Yeo, Q. Q.; Ko, Y.
Abstract: Aim: To review and evaluate the most recent literature on the economic outcomes of pharmacist‐managed services in people with diabetes. Background: The global prevalence of diabetes is increasing. Although pharmacist‐managed services have been shown to improve people's health outcomes, the economic impact of these programmes remains unclear. Methods: A systematic review was conducted of six databases. Study inclusion criteria were: (1) original research; (2) evaluation of pharmacist‐managed services in people with diabetes; (3) an economic evaluation; (4) English‐language publication; and (5) full‐text, published between January 2006 and December 2014. The quality of the full economic evaluations reviewed was evaluated using the Consolidated Health Economic Evaluation Reporting Standards checklist. Results: A total of 2204 articles were screened and 25 studies were selected. These studies were conducted in a community pharmacy ( n = 10), a clinic‐ /hospital‐based outpatient facility ( n = 8), or others. Pharmacist‐managed services included targeted education ( n = 24), general pharmacotherapeutic monitoring ( n = 21), health screening or laboratory testing services ( n = 9), immunization services ( n = 2) and pharmacokinetic monitoring ( n = 1). Compared with usual care, pharmacist‐managed services resulted in cost savings that varied from $7 to $65, 000 ($8 to $85, 000 in 2014 US dollars) per person per year, and generated higher quality‐adjusted life years with lower costs. Benefit‐to‐cost ratios ranged from 1:1 to 8.5:1. Among the 25 studies reviewed, 11 were full economic evaluations of moderate quality. Conclusions: Pharmacist‐managed services had a positive return in terms of economic viability. With the expanding role of pharmacists in the healthcare sector, alongside increasing health expenditure, future economic studies of high quality are needed to investigate the cost‐effectiveness of these services. What's new?: Although pharmacist‐managed services have been shown to improve health outcomes in people with diabetes, the economic impact of these programmes remains unclear. This systematic review identified and assessed 25 economic evaluations of these services. Pharmacist‐managed services included targeted education, general pharmacotherapeutic monitoring, health screening or laboratory testing services, immunization services and pharmacokinetic monitoring. Compared with usual care, pharmacist‐managed services were cost‐saving and generated higher quality‐adjusted life years with lower costs. Benefit‐to‐cost ratios ranged from 1:1 to 8.5:1. These services had a positive economic return. Future economic studies of high quality are needed to investigate the cost‐effectiveness of these services.